Analisa Sambaran Petir Terhadap Kinerja Arrester Pada Transformator Daya 150 kV Menggunakan Program ATP - Stevanny, Cecillia; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This study shows the effect of a lightning strike on the performance of lightning arresters at 150 kV power transformers. In the lightning strike case, there are several parameters that may affect to the arresters performance indicator, i.e the current charge and current quadratic integral . The analysis process is conducted by parameters modelling of transmission line and substation. The simulations are done by providing direct strike to the ground wire of 10 MV with a varies of the wave front time (Tf) and the duration of the strike (tau) of lightning impulse. To calculate the current charge and current quadratic integral of a wide variety of Tf and tau was involved trapezoidal numerical integration methods. Current charge and current quadratic integral that arise from direct strike and varies of Tf and tau compared to each phase in order to obtain the effect of Tf and tau lightning impulse on the performance of arresters as complied to the standard IEEE C62. 11. Keywords: current charge, current quadratic integral, trapezoidal numerical integration methods, arresters, ATP